COMPARATIVE ANALYSIS OF ELECTRONEUROMYOGRAPHIC CHANGES IN PATIENTS WITH CHEMOTHERAPY-INDUCED POLYNEUROPATHY ON THE BACKGROUND OF OVARIAN CANCER BEFORE AND AFTER THERAPY - N.N. Panjieva; N.K. Khaidarov; M.M. Raimova (Central Asian Journal of Medicine, 2024)
Chemoinduced polyneuropathy is a common side effect of chemotherapy, which significantly impairs the quality of life of patients. The purpose of this study is a comprehensive study of electroneuromyographic parameters in patients with chemotherapy-induced polyneuropathy before and after therapy during three 21-day courses of chemotherapy. The study included an analysis of changes in the functional state of peripheral nerves using electroneuromyography. This diagnostic method allows you to objectively assess the degree of nerve damage and the effectiveness of the therapeutic interventions used. The results of the study demonstrated significant changes in electroneuromyographic parameters in patients with CIPN after complex therapeutic interventions. The data obtained contribute to a better understanding of the pathophysiological mechanisms of CIPN and the development of more effective methods of treatment and prevention of this condition. The findings of the study highlight the need for regular monitoring of the condition of peripheral nerves in patients undergoing chemotherapy for timely detection and correction of CIPN, which ultimately helps to improve the quality of life of these patients.